2016
DOI: 10.1111/and.12714
|View full text |Cite
|
Sign up to set email alerts
|

Histological alterations in Leydig cells and macrophages in azoospermic men

Abstract: The study aimed to compare the histological features of Leydig cells and macrophages in the testicular interstitium of obstructive versus nonobstructive azoospermia. Thirty-nine azoospermic men undergoing testicular sperm extraction during intracytoplasmic sperm injection were allocated into obstructive azoospermia group (GI) and nonobstructive azoospermia group (GII) which was subdivided into Sertoli cell-only syndrome (GIIA), germ cell arrest (GIIB) and hypospermatogenesis (GIIC) subgroups. Serum LH, FSH and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…The results of IHC staining showed that CD68+ macrophages were sparsely distributed in the interstitial area of normal testis and near to the basal of seminiferous tubules (Figure 6A); Meanwhile, CD68+ macrophages were in a diffusely infiltrated state in NOA samples (Figure 6A). Consistent with earlier research results, 48 there was no significant difference in the expression of CD68 between normal testis and NOA samples ( p = .5899) (Figure 6B). CD163+ cells with M2 macrophage phenotype were sparsely localized in the interstitial area of normal testis (Figure 6C).…”
Section: Resultssupporting
confidence: 92%
“…The results of IHC staining showed that CD68+ macrophages were sparsely distributed in the interstitial area of normal testis and near to the basal of seminiferous tubules (Figure 6A); Meanwhile, CD68+ macrophages were in a diffusely infiltrated state in NOA samples (Figure 6A). Consistent with earlier research results, 48 there was no significant difference in the expression of CD68 between normal testis and NOA samples ( p = .5899) (Figure 6B). CD163+ cells with M2 macrophage phenotype were sparsely localized in the interstitial area of normal testis (Figure 6C).…”
Section: Resultssupporting
confidence: 92%
“…Cells producing steroid hormones, such as Leydig cells have abundant smooth endoplasmic reticulum. Variable histologic alterations of Leydig cells in NOA testes, including increased cell volume or hypertrophic Leydig cells, with abundant smooth endoplasmic reticulum and/or abnormal Leydig cells, rich in smooth endoplasmic reticulum may explain the increase of the macromolecular content in NOA 34–36 …”
Section: Discussionmentioning
confidence: 98%
“…Variable histologic alterations of Leydig cells in NOA testes, including increased cell volume or hypertrophic Leydig cells, with abundant smooth endoplasmic reticulum and/or abnormal Leydig cells, rich in smooth endoplasmic reticulum may explain the increase of the macromolecular content in NOA. [34][35][36] It is already known that testicular volume reflects spermatogenic status. Based on a recently published systematic review, testicular volume proved the only significant predictive factor of successful sperm retrieval in NOA.…”
Section: Discussionmentioning
confidence: 99%
“…This is the first study to demonstrate that tissue-resident Mø produce sex steroids de novo. Testicular interstitial Mø have a unique niche in interdigitation contact with Leydig cells [ 55 , 56 ] and are constantly exposed to a high concentration of testosterone and cytokines, which regulate steroidogenesis and spermatogenesis in the interstitial compartment [ 26 ]. Therefore, P4 production by interstitial Mø is possibly influenced by this niche.…”
Section: Discussionmentioning
confidence: 99%